Different land management measures and climate change impacts on the runoff – A simple empirical method derived in a mesoscale catchment on the Loess Plateau. (September 2015) - Zhang, Lulu; Podlasly, Christian; Feger, Karl-Heinz; Wang, Yanhui; Schwärzel, Kai
Abstract: Large-scale vegetation restoration and climate change triggered a significant decline in runoff in the middle reaches of the Yellow River and its tributaries. This runoff decline intensifies inherent water shortage and results in more severe water use conflicts that are threatening sustainable development in the Loess Plateau. Innovative strategies for more water-efficient land management are essential. To this end, the factors controlling runoff were investigated using the upstream area of the Jing River as an example. Runoff was found to be mainly controlled by evaporative demand, precipitation, and land cover type. Budyko's frameworks were applied to predict the annual and long-term runoff; however, the effect of changes in land management ( e.g., afforestation) on runoff cannot be assessed due to lack of vegetation factors. Therefore, an empirical analysis tool was derived based on an existing relationship for runoff estimation. This method was found to be more effective in reproducing the annual and long-term runoff than others. The incorporation of temporal changes in land cover and form in approach enables the estimation of the possible impact of soil conservation measures ( e.g., afforestation or terracing). Our study highlights the importance of adaptive land management strategies for mitigating water shortage on the Loess Plateau. Highlights: Land cover, water and energy availability are decisive factors in controlling runoff. Incorporating these key processes in method gives prediction with high efficiency. Grassland mitigates the adverse effects on runoff than afforestation in arid area. Dryland requires innovative strategies for more water-efficient land management. Environment restoration needs to consider trade-offs between natural resources.